Optimalisasi Peran Mediator sebagai Upaya Perdamaian dalam Rangka Mengurangi Angka Perceraian di Pengadilan Agama Soreang Ditinjau dari Peraturan Perundang-Undangan Terkait - Elchika Zalfa Athalia Sopian; Hazar Kusmayanti; Pupung Faisal (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
The success of a peace effort through mediation is highly dependent on the strategy and skill of the mediator in reconciling couples who are about to divorce. The purpose of this study is to describe the factors related to the legal aspects regarding obstacles to the level of success of mediators as a peace effort in divorce cases and to formulate efforts to optimize the role of mediators in order to reduce the divorce rate in the Soreang Religious Court based on related laws and regulations. This writing uses a normative legal method with analytical descriptive research specifications. The author implements normative law to the facts and practices that occur in the field. Data collection techniques use literature and field studies to collect information on divorce case data and the role of mediators in the Soreang Religious Court. The results of this study indicate that first, the success of peace efforts in divorce cases in the Soreang Religious Court is influenced by various inhibiting factors, including the good faith of the parties who are less cooperative, the influence of legal counsel, the condition of the mediation room is less representative, the parties' lack of understanding of mediation, and the role of the mediator is less than optimal. Second, the mediator's skill and sincerity are the main supporting factors for achieving a successful mediation in the Soreang Religious Court. However, mediators still do not have sufficient skills and professionalism to explain and hold caucuses. This is addressed through education or training programs, as well as enforcement of mediator certification to ensure the quality, credibility, and professionalism of mediators in the Class IB Soreang Religious Court.